ANALYSIS OF EROSION AND SEDIMENTATION RATES AT KEBUN RAYA BANUA RESERVOIR AND KAMPUNG BANJAR RESERVOIR USING THE USLE METHOD - Maulidayanti, Sri; Novitasari, Novitasari; Sofia, Elma (Universitas Lambung Mangkurat, 2025)
The Kebun Raya Banua Reservoir and Kampung Banjar Reservoir serve as water retention areas and tourist attractions within the South Kalimantan Provincial Government office complex. Erosion and sedimentation can have detrimental impacts on these reservoirs, necessitating this study to determine the erosion and sedimentation rates of both. This research utilizes various data, including rainfall data, soil type data, topographic data, crop management data, and soil conservation data. The Universal Soil Loss Equation (USLE) method was employed to calculate erosion and sedimentation rates. Analysis results indicate that the Kebun Raya Banua Reservoir experiences an erosion rate of 79,486 tons/ha/year and a sedimentation rate of 25,980 tons/ha/year. Conversely, the Kampung Banjar Reservoir exhibits an erosion rate of 8,779 tons/ha/year and a sedimentation rate of 2,954 tons/ha/year. Keywords: Erosion, Sedimentation, USLE, Reservoir